Pemberdayaan Wanita Tani dalam Penyediaan Benih untuk Mendukung Urban Farming di Kelurahan Balumbang Jaya, Kota Bogor - Asmanur Jannah; Astryani Rosyad; Andi Masnang; Sari Anggarawati; Yunus Arifien; Dyah Budibruri Wibaningwati; Anna Fitriani; Faizal Maad; Agista Rosiana; Refatria Febrian Rhamdiani; Abi Bakri; Muhammad Jono (J-Dinamika : Jurnal Pengabdian Masyarakat, 2020)
The Department of Agriculture and Food Security of Bogor City encourages its residents to be able to maximize agricultural potential even though the available land is limited in order to improve food security and family welfare. Optimal use of any agricultural land by using superior seeds and appropriate technology through a production process that meets quality assurance standards and is environmentally sound. The availability of seeds is an important factor in the development of urban farming because seeds are one of the main production facilities in plant cultivation activities. Extension activities and seed production training for 15 members of the Dalima and Lestari Women's Farmer Group, Balumbang Jaya Village, West Bogor District, are expected to be able to increase the ability of farmer groups to be able to produce seeds independently both for their own and commercial needs. Extension activities on understanding the quality of seeds and training on good seed production methods, starting from selecting the level of fruit maturity in accordance with the criteria to be used as seeds, pre-processing, cleaning, sorting and drying seeds, as well as packaging and storing seeds are very enthusiastic to be followed by the women's group. farmers in Balumbang Jaya Village. The response of the women farmer groups to this activity was very satisfied and asked that this activity be developed into other commodities.